Strategi Perencanaan Obyek Wisata Kawasan Ternak Deturia di Kecamatan Kotabaru Kabupaten Ende - Maria Endang Jamu; Lambertus Langga (ANALISIS, 2019)
This study aims to establish a planning strategy in the Deturia livestock area in Kotabaru District to become a horse racing tourist attraction in Ende Regency. The research approach used is qualitative with qualitative descriptive data analysis techniques. Data collection techniques using questionnaires, interviews, and observations. Respondents in the study were the people around the area of ??livestock attraction Deturia. Based on the results of the SWOT analysis of Tourism Objects of Deturia Cattle in Kotabaru District shows its position in quadrant I, where Deturia Cattle attractions have a balanced opportunity and strength that has a wide and strategic area, so they can take advantage of opportunities that exist optimally. In quadrant I, the aggressive strategy is a very favorable position, where the aggressive strategy can support any aggressive growth policies.